ZAKAT DI INDONESIA; SEBUAH REFORMULASI PENGELOLAAN - Idrus Idrus (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2017)
This text is a conceptual study from the point of view of Islamic education, which tries to provide perspective from different side, this critical study is more to the reformulation of zakat is the effort of ijtihad in the field of zakat to further streamline the implementation of zakat in the context of space and time. The basic assumption of zalcat reformulation is that charity is a social service and its rules are still loaded with ijtihad. this paper will try to propose the reformulation of zakat in three fields. First, reformulate the sources of zakat. Second, the reformulation of zalcat management. Third, reformulate the distribution of zakat.